Optimization of the Diagnosis of Cytomegalovirus Infection in Young Children in an Outpatient Setting (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Relevance A feature of modern pathology in young children is the wide prevalence of herpesvirus group infections, which can be activated against the background of impaired immune defense, thereby providing an additional immunosuppressive effect and causing general sensitization of the body Cytomegalovirus infection (CMVI) is caused by the opportunistic intracellular herpesvirus type 5 (HHV-5) [2].